2013
DOI: 10.1155/2013/651530
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders among Children and Adolescents Admitted to a French Psychiatric Emergency Service

Abstract: The aim of this study was to describe the characteristics of children and adolescents admitted to the psychiatric emergency department (ED) of a French public teaching hospital over a six-year study period (2001–2006). Data for all episodes of care in the psychiatric ED from January 1, 2001, to December 31, 2006, delivered to adolescents aged less than 18 years were retrospectively analyzed. During the six-year study period, 335 episodes of care in the psychiatric ED were experienced by 264 different adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
4
18
1
1
Order By: Relevance
“…The greater need for admission among adolescents coming from urban areas in our sample replicates previous studies reporting similar results in different cultures (Case et al, 2007;Grupp-Phelan et al, 2009; Llanes-Alvarez et al, 2019) and might, together with higher parent education, re ect more family awareness and easier access to service but might also re ect more behavioral problems with urbanization. However, the percentage of male patients (75%) in our sample was higher than expected from the actual percentage of male children in our population (51.2%) and from previous studies in other parts of the world (Boyer et al, 2013;Case et al, 2007;Llanes-Alvarez et al, 2019). This high percentage might re ect the cultural tendency to give attention to behavioral problems more in males rather than in females.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…The greater need for admission among adolescents coming from urban areas in our sample replicates previous studies reporting similar results in different cultures (Case et al, 2007;Grupp-Phelan et al, 2009; Llanes-Alvarez et al, 2019) and might, together with higher parent education, re ect more family awareness and easier access to service but might also re ect more behavioral problems with urbanization. However, the percentage of male patients (75%) in our sample was higher than expected from the actual percentage of male children in our population (51.2%) and from previous studies in other parts of the world (Boyer et al, 2013;Case et al, 2007;Llanes-Alvarez et al, 2019). This high percentage might re ect the cultural tendency to give attention to behavioral problems more in males rather than in females.…”
Section: Resultscontrasting
confidence: 80%
“…A recent study from Spain also reported an increase of youth under 18 years old admitted to psychiatric units from 27,7 per 100000 inhabitant in 2005 to 49.8 per 100000 inhabitant in 2015 (Llanes-Alvarez et al, 2019). In a study carried out in a French public hospital, 2.0% of the children and adolescents cared for in the emergency department were admitted to the psychiatric emergency department (Boyer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the US, among 100,000 admissions per year of patients, aged between six and 18, 418 psychiatric admissions were recorded. 8 11 The number of psychiatric emergency consultations of pediatric patients has significantly increased in Europe also, 12 14 in particular in Italy, 15 where an increase of 38% in psychiatric visits in emergency room has been recorded from 2001 to 2004 16 for the following causes: conduct disorders, substance and alcohol abuse, severe anxiety disorders, and eating disorders. 17 Self- or hetero-aggressive behavior is one of the most frequent reasons for psychiatric hospitalization of adolescents, probably because it can be difficult to control in family or community environments.…”
Section: Introductionmentioning
confidence: 99%
“…La prevalencia de TS y TC sería mayor a lo precisado, pues su expresión convoca diversas subespecialidades pediátricas en donde suelen infradiagnosticarse, pero su reporte ha aumentado en las dos últimas décadas 3 , representando un desafío diagnóstico y terapéutico para el médico por su dificultad clínica y general desconocimiento; así, en un estudio de Ndukuba et al, sólo 3% de los pediatras conocía adecuadamente los TC 4 , los que suelen sentirse molestos o manipulados por este tipo de pacientes 5 . Por otra parte, un estudio francés verificó que los principales motivos de consulta en un servicio de emergencias psiquiátricas fueron los trastornos neuróticos y somatomorfos 6 , hecho corroborado para la población general británica, donde los desórdenes mentales más prevalentes en 2010 fueron los del espectro somatomorfo, ansioso y afectivo 7 , por lo que el gasto público y privado en salud es prominente 5 , al asociarse a consultas reiteradas a múltiples especialistas, encontrándo-se mayoritariamente hallazgos negativos 8 . Adicionalmente, los criterios diagnósticos son aún controversiales en su aplicación infantojuvenil 9 , considerando además una falta de instrumentos evaluativos confiables y válidos y el poco consenso en relación a su manejo 10 .…”
Section: Introductionunclassified